Mid-term results of water vapor thermal therapy in patients with lower urinary tract symptoms related to benign prostatic hyperplasia - Ghahhari, Jamil; Sountoulides, Petros; Campobasso, Davide; Faieta, Alessio; Sessa, Francesco; Viola, Lorenzo; Siena, Giampaolo; Cianci, Filippo; Cindolo, Luca (Frontiers in Urology, 2022)
Objective: To evaluate short- and mid-term results of water vapor thermal therapy (WVTT) for LUTS due to BPH. Methods: Patients with LUTS due to to BPH who underwent WVTT from September 2019 onwards were included in this prospective, single-center study. Data regarding functional and sexual outcomes evaluated by validated questionnaires as well as uroflowmetry, urinalysis and culture, digital rectal examination, serum prostate specific antigen, transrectal ultrasound. The patients were followed at 3-6-12 and 18 months after the procedure. Results: 84 men in total were treated. Mean (± SD) prostate volume, operative time and hospital stay were 76,9±26,3 ml, 14 ± 18,5 minutes and 0,9 ± 0,7 days, respectively. The catheter was removed after 7±4,4 days. A significant (p < 0.05) improvement in Qmax, IPSS, QoL, OAB-q SF, ICIQ-SF and IIEF- 5 from baseline at last follow up (18 months) was recorded. 90% of patients reported a significantly improvement in ejaculatory function (de novo dry ejaculation in 4 patients). Early (≤30 days) post-operative complications were reported in 70% of patients, all grade 1 according to Clavien–Dindo. No late (>30 days) Clavien >1 procedure-related complications occurred. Three patients required re-operation (from 6 to 12 month after surgery). Conclusion: Water vapor thermal therapy is an effective and safe treatment for the management of LUTS due to BPH in the short- and mid-term follow-up, providing negligible sequelae on ejaculation.